Kajian Karakter Agronomi dan Daya Hasil Beberapa Varietas Unggul Baru Padi di Provinsi Bali - Sari, Anella Retna Kumala; Hidayah, Ifti Nur; Astika, I Made (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
A part from being famous for its tourism sector, Bali also has a special attraction in its agricultural sector, namely the subak system which has become a world cultural heritage. The sustainability of the Subak must be maintained, one of effort to create it is by maintaining the sustainability of land availability for food production through increasing the rice yields by using superior rice varieties that have the potential to increase farmers' income. Therefore, this study aims to examine the agronomic performance and yield of various superior rice varieties produced by Balitbangtan in the Bali Province. The study was carried out in the area of Bali Province namely Denpasar, Badung, Bangli, Buleleng, Gianyar, Karangasem and Jembrana in 2019 using Randomized Block Design consisting of various superior rice varieties treatments produced by Balitbangtan and cultivated by implementation the Integrated Crop Management technology on 0,5 ha land area in each area namely Towuti, Inpari-16, Inpari-20, Inpari-28, Inpari-43, Inpari-22, Inpari-32, Inpari-33 and the Cigeulis variety as a comparison and repeated five times. The results showed that all the superior rice varieties examined had great adaptability, growth and development were relatively as same as the Cigeulis variety. In addition, all superior rice varieties produced significantly greater yields than the Cigeulis variety therefore it could be considered as substitute for the use of the Cigeulis variety in Bali, especially the Inpari-28 variety which reached 8.24 t/ha, Â± 3 t/ha higher than the Cigeulis variety.